Revolutionizing High‐Areal‐Capacity Silicon Anodes With a Multi‐Level Carbon Construction Strategy for Practical Li‐Ion Batteries - Yongbiao Mu; Chaozhu Huang; Youqi Chu; Huicun Gu; Xianbing Wei; Xinyu Chen; Shaowei Kang; Jian Chen; Yichun Wang; Pengcheng Zhou; Ke Ge; Qing Zhang; et al. (Carbon Energy)
ABSTRACT There is an urgent need to develop high‐areal‐capacity silicon (Si) anodes with good cycling stability and rate capability for high‐energy‐density lithium‐ion batteries (LIBs). However, this remains a huge challenge due to large volume expansion‐induced mechanical degradation and electrical connectivity loss in thick electrodes. Here, a three‐in‐one strategy is proposed to achieve high‐areal‐capacity silicon anodes by constructing a multi‐level interconnected 3D porous and robust conductive network that carbon nanofibers and vertical carbon nanosheets tightly encapsulate on the surface of Si nanoparticles (Si NPs) anchored in porous carbon felts. This network accommodates large volume expansion of Si NPs to significantly improve electrode mechanical stability and creates excellent electrical connectivity to boost charge transport in thick electrodes, revealed through Multiphysics field simulations and in situ electrochemical techniques. Therefore, the designed Si anodes achieve superior long‐term stability with a capacity of 8.13 mAh cm−2 after 500 cycles and an ultrahigh areal capacity of 45.8 mAh cm−2. In particular, Ah‐level pouch cells demonstrate an impressive capacity retention of 79.34% after 500 cycles at 1 C. Our study offers novel insights and directions for understanding and optimizing high‐areal‐capacity silicon–carbon composite anodes.